2019
DOI: 10.1080/1331677x.2018.1545596
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency dynamics of the Croatian banking industry: DEA investigation

Abstract: The paper deals with the efficiency dynamics of the Croatian banking industry, covering the period from 2006 to 2015. We have implemented the intermediation approach, using interest and non-interest expenses and revenues as the input and output variables, respectively. The variable return to scale (BCC) Data Envelopment Analysis (DEA) output-oriented model has been implemented, and we have estimated the crisis-driven efficiency trends, as well as the impact of the EU membership. We further estimated the effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 14 publications
2
17
0
5
Order By: Relevance
“…De acuerdo con la revisión de la literatura, una de las razones que puede explicar la baja cantidad de unidades eficientes en el mercado accionario colombiano, en comparación con otros mercados de la misma índole, es el crecimiento económico. Es decir, que entre mayor sea el porcentaje de crecimiento de un país, la cantidad de unidades eficientes también tiende a aumentar (Davidovic et al, 2019;Paleèková, 2015). En este sentido, el crecimiento económico promedio de Colombia en el periodo de análisis fue de 3,26 %, mientras que en los países revisados (Irán y Malasia) fue en promedio de 3,81 %; lo anterior según datos de la plataforma oficial del Banco Mundial.…”
Section: Discussionunclassified
“…De acuerdo con la revisión de la literatura, una de las razones que puede explicar la baja cantidad de unidades eficientes en el mercado accionario colombiano, en comparación con otros mercados de la misma índole, es el crecimiento económico. Es decir, que entre mayor sea el porcentaje de crecimiento de un país, la cantidad de unidades eficientes también tiende a aumentar (Davidovic et al, 2019;Paleèková, 2015). En este sentido, el crecimiento económico promedio de Colombia en el periodo de análisis fue de 3,26 %, mientras que en los países revisados (Irán y Malasia) fue en promedio de 3,81 %; lo anterior según datos de la plataforma oficial del Banco Mundial.…”
Section: Discussionunclassified
“…Studies regarding the efficiency of commercial banks in North Macedonia and Croatia using the DEA methodology are not very common. There are six studies assessing the relative efficiency of Macedonian commercial banks with DEA: Cvetkoska (2010), Micajkova and Poposka (2013), Naumovska and Cvetkoska (2014), Naumovska andCvetkoska (2016), Fotova Čiković and and Cvetkoska and Fotova Čiković (2020) on one hand, and seven studies regarding the efficiency of the Croatian banking sector: Jemrić and Vujčić (2002), Toçi (2009), Jurčević and Mihelja Žaja (2013), Tuškan and Stojanović (2016), Kordić and Višković (2018), Pavković et al (2018) and Davidovic,et. al.…”
Section: The Banking System In Croatiamentioning
confidence: 99%
“…The most recent study is by Davidovic et al (2019). They give new insights regarding the impact of EU accession on bank efficiency.…”
Section: The Banking System In Croatiamentioning
confidence: 99%
“…The outcome of the study concluded that the major cause of inefficiency within public banks is scale inefficiency. Davidovic et al (2019) studied the estimated efficiency score of Croatian banking industry and identified the importance of certain banking-related variables such as origin of capital, market size and ownership structure. Rakshit (2019) investigated the performance level of Indian commercial banks by developing the two-stage radial DEA framework, which measures profitability and marketability functions of banks.…”
Section: Literature Reviewmentioning
confidence: 99%